THE ROLE OF UNDUE INFLUENCE AND UNCONSCIONABILITY AS MECHANISMS AGAINST UNFAIR CONTRACTS - Annisa Syaufika Yustisia Ridwan (Faculty of Law, Parahyangan Catholic University, 2026)
The growing recognition of undue influence in Indonesian contract law has introduced a new basis for invalidating agreements beyond traditional defects of consent. Originating from the common law tradition, the doctrine of undue influence shares conceptual similarities with the doctrine of unconscionability, particularly in addressing contractual injustice and power imbalances between parties. This article aims to examine the similarities and differences between the doctrines of undue influence and unconscionability in protecting parties against unfair contractual arrangements. This normative legal research employs a conceptual approach and relies on qualitative analysis of secondary data consisting of primary and secondary legal materials. Through a comparative examination of both doctrines, the study identifies their common objective of protecting weaker parties from exploitation arising from unequal bargaining positions and defective bargaining processes, which are ultimately reflected in the substantive terms of a contract. The analysis further demonstrates that the two doctrines differ in their primary focus of protection, available remedies, and scope of application. These distinctions have important implications for the development of Indonesian contract law and the protection of parties in unequal contractual relationships.